1991
DOI: 10.1017/s0022112091001040
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of oscillating flow around a circular cylinder

Abstract: This paper presents results obtained from a numerical solution to a stream function–vorticity formulation of the Navier–Stokes equations for the flow around a circular cylinder in planar oscillating flow at small Keulegan–Carpenter numbers (KC) in the subcritical Reynolds number (Re) range. The equations are solved by finite-difference methods. For very small KC ([les ] 1), the numerical results coincide with analytical solutions. As KC is increased, the incipient separation and instability leading to an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
73
1
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(86 citation statements)
references
References 19 publications
11
73
1
1
Order By: Relevance
“…Also, the length of the separated zone is relatively independent of KC. This is in contrast to higher Reynolds number (Re > 100) studies [6][7][8] where vortex formation and shedding are primarily dependent on KC.…”
contrasting
confidence: 65%
See 2 more Smart Citations
“…Also, the length of the separated zone is relatively independent of KC. This is in contrast to higher Reynolds number (Re > 100) studies [6][7][8] where vortex formation and shedding are primarily dependent on KC.…”
contrasting
confidence: 65%
“…Few studies [6][7][8] have been reported in the literature on the pulsatile flow past the stationary cylinder for Reynolds number (Re) >100 focusing on marine applications. As TAL operating Reynolds number is between 5 and 10, flow dynamics is expected to be different and no correlation can be made from studies available in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary layer has been theoretically predicted and often experimentally confirmed on large structures for both longitudinal and transverse oscillatory flows (Raney et al, 1954;Bertelsen et al, 1973;Williamson, 1985;Obasaju et al, 1988;Justesen, 1991;Tatsuno and Bearman, 1990). These studies were, however, conducted for Reynolds and Strouhal numbers very different from those of biological relevance, with the exception of the studies by Holtsmark et al (Holtsmark et al, 1954) and Wang (Wang, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Dalton 10 obtained a ®nite difference solution of the Navier±Stokes equations for KC 1±12 and Re 100±3000. Justesen 11 conducted a detailed computational study of planar oscillatory¯ow, also employing the ®nite difference technique, for b ranging between 196 and 1035 and KC extending up to 26. He observed various vortex-shedding regimes when KC exceeded approximately 7, while his computed drag values were very similar to those predicted by Wang 7 for KC extending up to 1Á5 for b 1035 and up to 2 for lower values of b.…”
Section: Introductionmentioning
confidence: 99%